Trajectory controllability of fractional-order α ∈(1,2] systems with delay - Srinivasa, V.; Sukavanam, N. (Journal of Applied Nonlinear Dynamics, 2026)
This paper is concerned with trajectory controllability of a class of fractional-order systems of order α ∈ (1,2] with delay in state variable and with a nonlinear control term. Firstly, the existence and uniqueness of the system is proved under suitable conditions on the nonlinear term involving state variable. Then the trajectory controllability of this class of systems is studied using Mittag-Leffler functions and Gronwall-Bellman inequality. Finally, examples are given to illustrate the proposed theory.